2005
DOI: 10.1007/s00210-005-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of erythrocyte “apoptosis” by catecholamines

Abstract: Osmotic shock, oxidative stress and Cl- removal activate a non-selective Ca2+-permeable cation conductance in human erythrocytes. The entry of Ca2+ leads to activation of a scramblase with subsequent exposure of phosphatidylserine at the cell surface. Phosphatidylserine mediates binding to phosphatidylserine receptors on macrophages which engulf and degrade phosphatidylserine exposing cells. Moreover, phosphatidylserine exposure may lead to adherence of erythrocytes to the vascular wall. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 60 publications
0
28
0
1
Order By: Relevance
“…The catecholamines dopamine, isoproterenol and epinephrine have similarly been shown to inhibit the Ca 21 -permeable cation channels and thus again to counteract eryptosis (101). Accordingly, catecholamines reverse the toxicity of cyclophosphamide (102).…”
Section: Inhibitors Of Eryptosismentioning
confidence: 99%
“…The catecholamines dopamine, isoproterenol and epinephrine have similarly been shown to inhibit the Ca 21 -permeable cation channels and thus again to counteract eryptosis (101). Accordingly, catecholamines reverse the toxicity of cyclophosphamide (102).…”
Section: Inhibitors Of Eryptosismentioning
confidence: 99%
“…Eryptosis is triggered by activation of Ca 2+ -permeable erythrocyte cation channels [30][31][32] -sensitive scrambling of the cell membrane [35] with phosphatidylserine exposure at the cell surface [30]. Eryptosis is further elicited by ceramide (acylsphingosine) [36].…”
Section: Introductionmentioning
confidence: 99%
“…L-DOPA decarboxylase is a PLP-dependent enzyme participating in the catecholamine biosynthesis pathway, responsible principally for the synthesis of the key neurotransmitters DA and 5-HT (Christenson et al, 1972). Biogenic amines are generally considered to participate in various processes, such as angiogenesis, cell proliferation, differentiation and apoptosis (Berry et al, 1996;Medina et al, 1999;Lang et al, 2005), which implies a potentially significant role of DDC in cancer pathobiology and progression. Interestingly enough, it has recently been shown that catecholamines, including DA itself, inhibit erythrocyte apoptosis by preventing scramblase activation and subsequent phosphatidylserine exposure on the cell membrane (Lang et al, 2005), which in turn triggers clearance of apoptotic cells by macrophages.…”
Section: Discussionmentioning
confidence: 99%